Installation of the flight data recorder S2-3a on Su-22 and MiG-29 aircraft - Tomyślak Adam (MATEC Web of Conferences, 2024)
The S2-3a flight data recording system developed at the Air Force Institute of Technology is intended for recording the flight parameters and the operating parameters of aircraft assemblies, as well as to store the recorded data in its memory to evaluate flight safety, piloting technique, technical condition of on-board system and air accident (air crash) causes. S2-3a flight data recording systems are operated on-board the: TS-11 ISKRA, PZL-130 TC-II ORLIK, M-28 BRYZA, MiG-29, and Su-22 aircraft, as well as the Mi-8, Mi-14, Mi-17, Mi-24, W-3 SOKÓŁ and SW-4 helicopters. The paper contains selected information on the instllation of the S2-3a recorder on Su-22 and MiG-29 aircraft AT the Military Aviation Works no. 2 S.A. In Bydgoszcz.